(untitled) (Legislatif, 2020)
Abstract The presence of cybercrime has been a threat to human life, making it difficult for governments to keep up with computer technology, particularly the internet. This is the result of rapid developments in information technology, so each development essentially has both a positive and negative impact. One negative effect is the misuse of data and personal information. The human world’s weaknesses are not notwithstanding the lack of regulation or no regulation on cybersecurity and personal data protection, resulting in confusion among members of society. Therefore, a system that addresses this problem requires, the Indonesian Data Protection System (IPDS) I a system that guarantees and provides personal data and information management security/ it aims to know how to manage personal information data in Indonesia today, and to learn how formulations for data management and personal information via Indonesian Data Protection System (IPDS) as a cyber surveillance and data protection effort, the study adopted a normative juridical method with the State Approach. To this issue, the authors concluded, first, that it would require a rule relating to cybercrime as well as protection data and personal information in Indonesia. Second, there is a system that will address the problem of cybercrime especially in the field of data management and personal information of the Indonesian Data Protection System (IPDS). Keywords: Indonesian Data Protection System (IPDS); Cyber Crime; Personal Information and Data Protection; Abstrak Adanya Kejahatan Siber (cybercrime) telah menjadi ancaman diberbagai kehidupan manusia, sehingga pemerintah sulit mengimbangi teknik kejahatan yang dilakukan dengan teknologi komputer, khususnya jaringan internet. Hal ini merupakan akibat dari pesatnya perkembangan teknologi informasi, sehingga setiap perkembangan pada hakikatnya membawa dampak yang positif maupun negatif. Salah satu dampak negatifnya adalah adanya penyalahgunaan data dan informasi pribadi. Kelemahan dunia siber tidak terlepas dari kurangnya pengaturan atau belum adanya regulasi mengenai kemanan siber dan perlindungan data pribadi, sehingga menimbulkan kerancauan ditengah-tengah anggota masyarakat. Oleh karena itu, dibutuhkan sebuah sistem yang mampu mengatasi masalah tersebut, sistem Indonesia Data Protection System (IDPS) adalah sebuah sistem yang menjamin serta memberikan keamanan pengelolaan data dan informasi pribadi. Penelitian ini bertujuan untuk mengetahui bagaimana Problematika Pengelolaan data informasi pribadi di Indonesia saat ini, dan untuk mengetahui bagaimana formulasi pengelolaan data dan informasi pribadi melalui Indonesian Data Protection System (IDPS) Sebagai Upaya Cyber Surveillance and Data Protection. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan peraturan perundang-undangan (Statute Approach). Terhadap isu ini, penulis menyimpulkan, Pertama, dibutuhkan sebuah peraturan yang berkaitan dengan kejahatan dunia maya (cybercrime) dan juga perlindungan data dan informasi pribadi di Indonesia. Kedua, dibutuhkan sebuah sistem yang mampu mengatasi permasalahan kejahatan dunia maya khususnya dibidang pengelolaan data dan informasi pribadi yaitu Indonesian Data Protection System (IDPS). Kata Kunci: Indonesian Data Protection System; Kejahatan Sibern (Cybercrime); Perlindungan Data dan Informasi Pribadi;